Labor Transformation in the Agricultural Sector in Riau Province - Khairunas; Syapsan; Tambupolon, Dahlan (Future Science / FSH-PH Publications, 2024)
One of the efforts to increase economic added value is through economic structure transformation. The impact of the transformation of the economic structure is the transformation of workforce. Economic transformation that is not accompanied by labor transformation can result in lower incomes for workers in the agricultural sector and a scarcity of labor in the non-agricultural sectors. The goal of this research is to analyze the transformation of the workforce structure in Riau Province and to build a model that can explain the transformation of the workforce structure in Riau Province during 2018-2023. Using panel regression analysis, this research found that the GRDP ratio and average years of schooling had a linear positive effect on the transformation of labor structure. Thus, it can be said that these two variables can encourage workforce transformation in Riau Province. Regarding the various results obtained, there are several policy suggestions and recommendations that can be given to related parties.